Prophetic Medicine-Nigella Sativa (Black cumin seeds) - Potential herb for COVID-19? - Naina Mohamed Pakkir Maideen (Korean Pharmacopuncture Institute, 2020)
Coronavirus disease-19 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS CoV-2). Currently, the management of patients with COVID-19 depends mainly on repurposed drugs which include chloroquine, hydroxychloroquine, lopinavir/ritonavir, ribavirin, remdesivir, favipiravir, umifenovir, interferon-α, interferon-β and others. In this review, the potential of Nigella sativa (black cumin seeds) to treat the patients with COVID-19 analyzed, as it has shown to possess antiviral, antioxidant, anti-inflammatory, anticoagulant, immunomodulatory, bronchodilatory, antihistaminic, antitussive, antipyretic and analgesic activities. PubMed, Google Scholar, Science Direct, Directory of open access journals (DOAJ) and reference lists were searched to identify articles associated with antiviral and other properties of N.sativa related to the signs and symptoms of COVID-19. Various randomized controlled trials, pilot studies, case reports and in vitro and in vivo studies confirmed that N.sativa has antiviral, antioxidant, anti-inflammatory, immunomodulatory, bronchodilatory, antihistaminic, antitussive activities related to causative oraganism and signs and symptoms of COVID-19. N. sativa could be used as an adjuvant therapy along with repurposed conventional drugs to manage the patients with COVID-19.